STUDI KOMPARATIF PEMIKIRAN H. HUSIN QADERI DAN H. M. ZURKANI JAHJA TENTANG KONSEP AL ASMÃ AL-HUSNÃ YANG MENUNJUKKAN PERBUATAN ALLAH - Ainah, Nor; Abidin, M. Zainal (Jurnal Studia Insania, 2014)
This paper compared the tought of al-Asma al-Husna by H. Husin Qader and H.M. Zurkani Jahja. There are differences in the tought of the two figures in the delivery of the words of al-Asma al-Husna written in their work. H. Husin Qaderi in his book âSenjata Mukminâ (the Faithfulâs weapon) and H.M. Zurkani Jahja in his book â99 jalan menuju Tuhanâ (99 ways of finding the God). The findings of this study is H. Husin Qaderi thought about al-Asma al-Husna that shows Godâs action is the dominant to the practical prayer with âzikirâ, it is appropriate approach to Sufism that he had as well as the community needs are preaching at that time. H. M. Zurkani Jahja told about al-Asma al-Husna that shows Godâs action is the dominant to the moral and spiritual implications, the Sufism approach that he used in accordance with al-Ghazali in his âal-MaqsÃ¢d. Zurkani used simple and easy explanation, it is because he wrote al-Asma al-Husna in a tabloid then booked, his expectation was the people to behave like the personality of God limited his ability. There are differences of tought about al-Asma al-Husna showing the actions of God according to both of them, their difference lies in the Godâs blessings on His servants. Qaderi more closed, while Zurkani seems more open to Godâs faithful servant and vice versa to get Godâs blessings.